Disruption of technologies in the classroom according to the unified theory of technology acceptance and use - Pilapaxi-Cunalata, Nancy (2025)
The use of technologies in the classroom has been a topic of growing interest in contemporary education. The research study explores the disruption caused by technologies in the educational environment from the perspective of the Unified Theory of Acceptance and Use of Technology (UTAUT). UTAUT provides a comprehensive framework for understanding how students in an educational unit adopt and use technologies, considering social, psychological, and contextual factors. From this perspective, it examines the various impacts that the introduction of technologies can have on the classroom, including changes in the dynamics of learning, student-teacher interaction, and the overall effectiveness of the educational process. In the bibliographic review, a bibliometric analysis was performed using the Web of Science database from 2020 to 2024 in English language, obtaining 720 articles in total, then graphical representations were made with VOSviewer to distinguish the countries and authors with greater scientific contribution in the field of the adoption of technologies in the classroom according to the Unified Theory of Acceptance and Use of Technology. A continuous growth in studies involving the UTAUT method was observed, highlighting Malaysia, People's Republic of China, and Saudi Arabia. In addition, the practical implications of UTAUT for designing and implementing effective technology integration strategies in education were explored to maximize benefits and mitigate potential challenges. This analysis contributes to a deeper understanding of how technologies are transforming teaching and learning and provides guidance for effectively adapting to these changes in the modern classroom.